Deleuze et Leibniz: dans les plis de la pensée baroque: Делез и Лајбниц: во диплите на барокната мисла - Dimiškovska-Trajanoska, Ana; Angelovska, Jeanne (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Ana Dimiškovska-Trajanoska | Ана Димишковска-Трајаноска Title (French): Deleuze et Leibniz: dans les plis de la pensée baroque Title (Macedonian): Делез и Лајбниц: во диплите на барокната мисла Translated by (Macedonian to French): Jeanne Angelovska | Жан Ангеловска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 261-282 Page Count: 21 Citation (French): Ana Dimiškovska-Trajanoska, “Deleuze et Leibniz: dans les plis de la pensée baroque,” traduit du macédonien par Jeanne Angelovska, Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 261-282. Citation (Macedonian): Ана Димишковска-Трајаноска, „Делез и Лајбниц: во диплите на барокната мисла“, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 261-282.